Do We Have the Right Performance Indicators for the Circular Economy?: Insight into the Swiss Waste Management System. (29th October 2016) - Haupt, Melanie; Vadenbo, Carl; Hellweg, Stefanie
Summary: A material flow analysis of the 2012 Swiss waste management system is presented, highlighting the material content available from waste. Half of municipal solid waste (MSW) is materially recycled and the other half thermally treated with energy recovery. A key component of an industrial ecosystem is increasing the resource efficiency through circulating materials. Recycling rates (RRs), an indicator for the circulating behavior of materials, are often used as measure for the degree of circularity of an economy. This study provides an in‐depth analysis of the recycling of paper, cardboard, aluminum, tinplate, glass, and polyethylene terephthalate (PET) from MSW in Switzerland by splitting the RRs into closed‐ and open‐loop collection rate (CR) and RRs. Whereas CR refers to collected material that enters the recycling process, RRs measure the available secondary resources produced from recycling processes. For PET, the closed‐loop CR of 45% and the open‐loop CR of 40% compare to an RR of 31% and 37%, respectively (including exports and recycling of polyethylene and metals from collection). Official collection rates for paper and cardboard are very high (97%), whereas CR of 74% and 89% and RR of 59% and 81% for paper and cardboard, respectively, were found in the present study (including export). For a majority of the separately collected materials investigated, the rates that are determined are substantially lower than those that are officially communicated. Furthermore, given that official rates often do not provide information on the availability of secondary materials, the improvement potential for increased resource recovery is hidden.